FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENGETAHUAN IBU HAMIL TENTANG KEPUTIHAN DI WILAYAH KERJA PUSKESMAS KOTA JANTHO ACEH BESAR TAHUN 2023 - Yanti, Sulis Marda; Kurniawati, Putri; Saudah, Saudah; Susanti, Dewina; Putri, Risa Yennisa; Susanti, Mesra; Sabrina, Nadia (JURNAL ILMIAH DHDT - KEBIDANAN, 2023)
Vaginal discharge is excessive discharge from the birth canal or vagina. The incidence of vaginal discharge in women in the world reaches 75%, while in Indonesia women who experience vaginal discharge reach 70% including pregnant women. One of the complaints often encountered in clinics and maternal and child health (MCH) is vaginal discharge (fluor albus), 16% of patients with vaginal discharge are pregnant women, caused by candida albicans 53%, trichomonas 3.1% and classified by bacteria 40.1%. Candida albicans is the most common group found in patients with vaginal discharge. Objective To determine the factors associated with the knowledge of pregnant women about vaginal discharge in the Jantho City Health Center Area, Aceh Besar in 2023. The research method is analytical using a Cross Sectional approach conducted on July 8-11, 2023 in the Jantho City Health Center Area of Aceh Besar with a population of 30 pregnant women. The research instrument is a questionnaire. Data analysis using univariate and bivariate analysis with the SPSS statistical program. The results of statistical tests with Chi Square obtained p value = 0.14 (P<0.05) means there is a relationship between sources of information with knowledge, the results of statistical tests with Chi Square obtained p value = 0.001 (P<0.05) means there is a relationship between age and knowledge, the results of statistical tests with Chi Square obtained p value = 0.000 (P<0.05) means there is a relationship between experience and knowledge, and the results of statistical tests with Chi Square obtained p value = 0.000 (P<0.05) means there is a relationship between education and knowledge. The conclusion is that there is no relationship between information sources and knowledge, and there is a relationship between age, experience, and education on knowledge.